Ovarian cancer targeted therapy: current landscape and future challenges - Wang, Guangli; Yang, Hui; Wang, Yuling; Qin, Juan (Frontiers in Oncology, 2025)
Ovarian cancer is one of the deadliest malignancies in women and remains the leading cause of death from gynecological cancers worldwide. The standard treatment typically involves tumor-reducing surgery and cytotoxic chemotherapy; however, many patients are unable to tolerate the side effects of these treatments or experience recurrence due to significant drug resistance, which limits the overall clinical benefits. Consequently, there is a pressing need for novel therapeutic strategies. In recent years, Targeted therapies, including anti-angiogenic drugs, PARP inhibitors, and immune checkpoint inhibitors, have revolutionized ovarian cancer treatment. Additionally, drug targeting and therapeutic efficacy have been substantially enhanced through carrier technologies and conjugation strategies, such as antibody-drug conjugates, polymer-drug conjugates, and dual-targeted nanomedicines. These innovative strategies aim to selectively target ovarian cancer cells, overcome drug resistance, and reduce systemic toxicity, thus achieving optimal therapeutic outcomes. This review aims to critically evaluate the progress and challenges in ovarian cancer targeted therapy and propose future research directions to improve clinical outcomes efforts toward providing more effective and personalized treatment options for ovarian cancer patients.